Community-based vigilante violence in sub-Saharan Africa: The role of corporate social responsibility in Nigeria's oil producing communities - Joseph Ikechukwu Uduji; Elda Nduka Okolo-Obasi; Damian Uche Ajah; Deborah Chinwendu Otei; Ozioma Happiness Obi-Anike; Samuel Chukwuemeka Ezuka; Emmanuel Ejiofor Nwamuo; Steve Emeka Emengini (African Governance and Development Institute (AGDI), 2024)
Nigeria's oil-producing region is experiencing a surge in community-based vigilante violence, potentially escalating conflict dynamics and increasing fear of injury. The reason it matters is that neighborhood vigilante groups are more likely to participate in criminal, political, and ethnic plotting and are not always controllable. This prompted us to look into whether GMoU cluster interventions by MOCs could lower the heat map of fatalities from vigilante violence in Nigeria's Niger Delta. The results of logit regression and propensity score matching demonstrate that the MOCs' limited CSR efforts to protect the area have been successful in creating, formalizing, equipping, and managing vigilante groups. The results also show that the CSR initiatives have reduced vigilante violence within and between host communities, as well as violence against their residents. This implies that raising awareness of CSR with the goal of strengthening vigilante control will strengthen the local security apparatus, discourage resurgence in the various rural areas, safeguard the workers and equipment of oil firms, and provide a favorable business environment in the area.
Keywords: 330; Vigilante violence; environmental justice; corporate social responsibility; oil producing communities; sub-Saharan Africa